First occurrence and whole‐genome comparison of Pseudomonas haemolytica isolated in farmed rainbow trout. (23rd June 2022) - Saticioglu, Izzet Burcin; Mulet, Magdalena; Duman, Muhammed; Altun, Soner; Gomila, Margarita; Lalucat, Jorge; García‐Valdés, Elena
Abstract: The isolation of Pseudomonas haemolytica from different habitats as well as its distribution over a wide geographical area, possible reservoir role for antibiotic resistance and zoonotic potential, all require the detailed characterization of P. haemolytica strains. In the present study, we describe 18 phenotypically similar strains isolated from the rainbow trout, Oncorhynchus mykiss (Walbaum, 1792). The strains were collected from seemingly healthy, symptomatic or moribund rainbow trout of all sizes, from fry to broodstock. The strains were morphologically, phenotypically (API20 NE and VITEK 2) and chemotaxonomically characterized by their methyl‐fatty acid content (FAME), and mass spectrometry (MALDI‐TOF) by their protein profiles. The 16S rRNA sequence similarity values grouped them into the Pseudomonas fluorescens phylogenetic group of species. The 18 strains were compared to 6 other previously described P. haemolytica strains, 2 of which were isolated from milk products and 4 from chicken products. A multilocus sequence analysis was performed for all strains. Strain P45 was selected to represent the 18 new isolates for genomic comparisons by ANIb, and GGDC was used to confirm the identification at species level. The presence of genes related to antimicrobial resistance, secretion systems and virulence was also assessed using comparative genomic analyses. This is the first comprehensive report on P. haemolytica strains isolated from fish.